POTENTIAL CHALLENGES AND THREATS ASSOCIATED WITH PINE NUT CULTIVATION AND MARKETING IN PAKISTAN - Aqsa Akhtar; Sipper Khan; RajaZoq ulArfeen; Nauman Khalid (Journal of Animal and Plant Sciences, 2023)
Pine nut or chilgoza pine (Pinus gerardiana) is considered one of the most valuable non-timber forest species (NTFP) of Pakistan. Pine nut is a rich source of many valuable food constituents including unsaturated fatty acids, sugar, vitamins and minerals. Due to the poor management policies and heavy exploitation, it has been listed as threatened species by the IUCN. Pine nuts lose their quality and nutritional value due to poor processing technologies that tend to lower their acceptability in big markets. In order to increase the market value of pine nuts, research institutes should work in collaboration to conserve this endangered valuable species by developing good quality pest-resistant seeds. Moreover, they should propose such treatments which help to extend the shelf life of pine nut seeds during processing and storage on a commercial level. Meanwhile,the government should launch new projects to understand the dynamics of the pine nuts life cycle together with sustainable conservation.
Keywords: Pine nut; chilgoza; marketing; natural regeneration; forest; Pakistan